Radicular cyst followed by incomplete pulp therapy in primary molar: A case report - C Nagarathna; A R Jaya; I Jaiganesh (Wolters Kluwer Medknow Publications, 2013)
Radicular cysts are one of the most common odontogenic cyst of the jaws. However, those arising from primary teeth are rare. An 8-year-old boy reported to the Department of Pedodontics and Preventive Dentistry with the chief complaint of pain and swelling on the lower left primary molar tooth region. Radiographic examination revealed a well-defined radiolucency with continuous hyperostotic border. Considering the age of the child, size of lesion, and involvement of unerupted premolars; marsupialization was preferred as a conservative treatment of choice. The success of the treatment was evident both clinically and radiographically during the follow-up period.